Active Immunotherapy of Cancer. (17th November 2015) - Chodon, Thinle; Koya, Richard C.; Odunsi, Kunle
Abstract : Clinical progress in the field of cancer immunotherapy has been slow for many years but within the last 5 years, breakthrough successes have brought immunotherapy to the forefront in cancer therapy. Promising results have been observed in a variety of cancers including solid tumors and hematological malignancies with adoptive cell therapy using natural host tumor infiltrating lymphocytes, host cells that have been genetically engineered with antitumor T-cell receptors or chimeric antigen receptors, immune checkpoint inhibitors like anti-CTLA-4, anti-PD-1 or PD-L1 monoclonal antibodies and oncolytic virus-based immunotherapy. However, most treatment modalities have shown limited efficacy with single therapy. The complex nature of cancer with intra- and inter-tumor antigen and genomic heterogeneity coupled with the immune suppressive microenvironment emphasizes the prospect of personalized targeted immunotherapy to manipulate the patient's own immune system against cancer. For successful, robust and long-lasting cure of cancer, a multi-modal approach is essential, combining anti-tumor cell therapy with manipulation of multiple pathways in the tumor microenvironment to ameliorate tumor-induced immunosuppression.